2016
DOI: 10.4103/0972-0707.181936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dentinal wall adaptation ability of MTA Fillapex using stereo electron microscope

Abstract: Background:An ideal root canal obturation requires a complete dentinal wall adaptation of sealer and Gutta-percha combinations without any gap formations.Aims:The aim of the study was to evaluate the dentinal wall adaptation ability of MTA Fillapex root canal sealer using stereo electron microscope (SEM).Methods:Twenty-four, single-rooted, human maxillary incisor teeth were used. All canals were prepared with a rotary nickel–titanium (Ni–Ti) instrument to a size F3 file. Teeth divided into two equal groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…These results come in accordance with Polineni et al (34). On the other hand, this result is come contradict to Demiriz et al 2016 (33), who reported no significant difference between root sections of MTA Fillapex and AH Plus. The difference in the result might be related to the use of the different obturation technique.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…These results come in accordance with Polineni et al (34). On the other hand, this result is come contradict to Demiriz et al 2016 (33), who reported no significant difference between root sections of MTA Fillapex and AH Plus. The difference in the result might be related to the use of the different obturation technique.…”
contrasting
confidence: 56%
“…Demiriz et al 2016 (33); stated that incomplete polymerization, viscosity increases during the polymerization or polymerization shrinkage could be the cause of gap formation in AH Plus and MTA Fillapex who had a resin component. In the current study, samples were stored for one week to be sure that sealers were set completely.…”
mentioning
confidence: 99%
“…Manufacturer claims that MTA Fillapex provides long-term sealing capacity and promotes the deposition of hard tissue at the root apex. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used root canal obturation materials are gutta percha points and sealant cements. 1,12,17,[20][21][22] Gutta percha points are composed of inert rubber with zinc oxide and silver additives. 1 They do not adhere to the tooth's dentinal walls 12,23 or prevent leakage through the canal.…”
Section: Introductionmentioning
confidence: 99%
“…Most endodontic failures are due to bacterial or irritant microleakage from the root canal into the surrounding periapical tissues due to an inadequate apical seal. [25][26][27][28][29] The combination of a gutta percha point and sealant cement should ideally create a tridimensional, hermetic, fluid-tight, bacterial-impervious seal, 12,14,18,20,[30][31][32] preventing recontamination of the canal and the apical migration of bacteria and irritants. 1,[14][15][16] An ideal root canal sealant should have certain characteristics.…”
Section: Introductionmentioning
confidence: 99%